Computed tomography diagnostics of mediastinal hernias after pneumonectomy - M. N. Vasyukov (Вестник хирургии имени И.И. Грекова)
The formation of mediastinal hernias after pneumonectomy may be associated with the development of complications from the remaining lung. The lack of information about the patterns of their development, morphometric characteristics, and dynamics in the postoperative period indicates the urgency of the problem.The OBJECTIVE was to reveal the topographic and anatomical patterns of the formation of mediastinal hernias after pneumonectomy, to give anatomometric characteristics at various times after the operation.METHODS AND MATERIALS. Computed tomography of the chest of 53 patients (50 men and 3 women) aged 39 to 75 years before and after pneumonectomy (26 on the left, 27 on the right) were examined. Computed tomography was performed on the 10–12th day, 6 and 12 months after surgery. The transverse size of anterior and posterior mediastinal hernias after left- and right-sided pneumonectomies, their dynamics, and density of lung tissue in the hernial protrusion area were studied. 3D was performed – modeling of the remaining lung. RESULTS. Hernial protrusions were visualized in patients with atelectasis of the lung part before surgery. 10 days after left pneumonectomy, anterior and posterior mediastinal hernias were visualized in 80.8 % of patients. One year after left surgery, anterior hernias were observed in 91.7 % of patients, they increased in size and the average size was (57.3±5.2) mm at the ThV–VI level. Posterior mediastinal hernias 12 months after left pneumonectomy were found in 80.5 % of patients, the average size was (34.9±5.2) mm at the ThVIII level. After right pneumonectomy in the early postoperative period, anterior mediastinal hernias occurred in 70.3 % of patients, a year later-in 88.2 %, the average size was (41.0±7.6) mm at the ThV level. The average transverse sizes of anterior mediastinal hernias 12 months after left and right pneumonectomies did not differ significantly (P=0.950). Posterior mediastinal hernias after right surgery were found in 20.0 % of patients, the largest size was determined at the ThIX level, with an average of (12.7±5.8) mm. After pneumonectomy, bullous changes occured in the lung tissue of mediastinal hernias.CONCLUSION. Anterior mediastinal hernias are equally common after left and right pneumonectomy, while the size of the hernias did not differ significantly. Posterior mediastinal hernias after left pneumonectomy occurs in 88.2 % of patients, after right pneumonectomy – in 20 % of cases.